The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s00134-014-3531-1
|View full text |Cite
|
Sign up to set email alerts
|

Crystalloid fluid therapy: is the balance tipping towards balanced solutions?

Abstract: Intravenous saline solutions were first introduced into clinical practice in the Sunderland cholera epidemic of 1831 [1]. More than 150 years later, not only is 0.9 % saline the most commonly used intravenous fluid in critically ill patients, it is also the fluid that has been administered to the largest number of critically ill patients in randomised controlled trials [2,3]. It is cheap and readily available, and more than a million litres of intravenous 0.9 % saline are administered to patients around the wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…However, the association between the development and accentuation of AKI and 0.9% saline administration in critically ill patients remains controversial, with data both supporting and rejecting the hypothesis [ 19 , 20 ]. A recent study failed to demonstrate a benefit of Plasma-Lyte on the incidence of AKI, but the mean fluid volume administered was only 2 L in 24 h, considerably less than in our study [ 10 ].…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…However, the association between the development and accentuation of AKI and 0.9% saline administration in critically ill patients remains controversial, with data both supporting and rejecting the hypothesis [ 19 , 20 ]. A recent study failed to demonstrate a benefit of Plasma-Lyte on the incidence of AKI, but the mean fluid volume administered was only 2 L in 24 h, considerably less than in our study [ 10 ].…”
Section: Discussioncontrasting
confidence: 87%
“…A 0.9% saline solution remains the most widely used intravenous fluid during the perioperative period, but recent data has emerged questioning its safety [ 6–8 ]. A 0.9% saline solution has been shown to reduce renal cortical blood flow in healthy volunteers [ 9 ], and animal studies have suggested that sustained renal vasoconstriction is specifically related to hyperchloraemia [ 10 ]. The high chloride load in 0.9% saline has also been shown to induce hyperchloraemic acidosis [ 11 ], and this in turn has been associated with the development and accentuation of postoperative AKI [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additional considerations were that the sodium in Hartmann solution contains calcium and was therefore incompatible with blood products preserved in citrate-based anticoagulation solutions, and that Hartmann solution contains more chloride than PL-148. 14 The composition of the study fluids is shown in eTable 1 in Supplement 2. Participating ICUs were assigned to use blinded study fluid (either saline or buffered crystalloid) for alternating treatment blocks of 7 weeks, with the initial fluid determined by the study statistician using computer-generated randomization.…”
Section: Study Randomization and Treatmentmentioning
confidence: 99%
“…Although some balanced solutions are calcium-free (i.e., Plasma-Lyte and Normosol-R), there are others that contain calcium such as Lactated Ringer's, which has a calcium concentration of 2 mmol/L (8 mg/dL) (Young & Joannidis, 2014). As long as the calcium concentration of the solution is less than the patient's serum calcium concentration, the solution can still be expected to lower calcium levels over …”
Section: Management Optionsmentioning
confidence: 99%